Heavy alcohol drinking and subclinical echocardiographic abnormalities of structure and function. Issue 1 (2nd June 2021) - Iakunchykova, Olena; Schirmer, Henrik; Leong, Darryl; Malyutina, Sofia; Ryabikov, Andrew; Averina, Maria; Kudryavtsev, Alexander; Kornev, Mikhail; Voronina, Ekaterina; Paramonov, Andrey; Wilsgaard, Tom; Leon, David
Abstract : Objective: The aim of the study is to assess changes in heart structure and function associated with heavy alcohol use by comparing echocardiographic indices in a population-based sample to those in patients admitted to an inpatient facility with severe alcohol problems. Methods and results: We used data from the Know Your Heart study (2015–2017) which is a cross-sectional study that recruited 2479 participants aged 35–69 years from the general population of the city of Arkhangelsk in Northwest Russia and 278 patients from the Arkhangelsk Regional Psychiatric Hospital with a primary diagnosis related to chronic alcohol use (narcology clinic subsample). The drinking patterns of the population-based sample were characterised in detail. We used regression models controlling for age, sex, smoking, education and waist to hip ratio to evaluate the differences in echocardiographic indices in participants with different drinking patterns. The means of left ventricular end-diastolic diameter and indexed left atrial systolic diameter were increased among heavy drinkers (narcology clinic subsample), while mean left ventricular ejection fraction was decreased in this group compared with the population-based sample. In contrast, the harmful and hazardous drinkers in the population-based sample did not differ from non-problem drinkers with respect to echocardiographic indices of systolic and diastolic function. Conclusions: Extremely heavy drinking is associated with a specific set of structural and functional abnormalities of the heart that may be regarded as precursors of alcohol-related dilated cardiomyopathy.